The PTP1B inhibitor MSI-1436 ameliorates liver insulin sensitivity by modulating autophagy, ER stress and systemic inflammation in Equine metabolic syndrome affected horses - Bourebaba, Lynda; Serwotka-Suszczak, Anna; Pielok, Ariadna; Sikora, Mateusz; Mularczyk, Malwina; Marycz, Krzysztof (Frontiers in Endocrinology, 2023)
Equine metabolic syndrome (EMS) is a multifactorial pathology gathering insulin resistance, low-grade inflammation and past or chronic laminitis. Among the several molecular mechanisms underlying EMS pathogenesis, increased negative insulin signalling regulation mediated by protein tyrosine phosphatase 1 B (PTP1B) has emerged as a critical axis in the development of liver insulin resistance and general metabolic distress associated to increased ER stress, inflammation and disrupted autophagy. Thus, the use of PTP1B selective inhibitors such as MSI-1436 might be considered as a golden therapeutic tool for the proper management of EMS and associated conditions. Therefore, the present investigation aimed at verifying the clinical efficacy of MSI-1436 systemic administration on liver metabolic balance, insulin sensitivity and inflammatory status in EMS affected horses. Moreover, the impact of MSI-1436 treatment on liver autophagy machinery and associated ER stress in liver tissue has been analysed. Clinical application of MSI-1436 to EMS horses restored proper adiponectin levels and attenuated the typical hyperinsulinemia and hyperglycaemia. Moreover, administration of MSI-1436 further reduced the circulating levels of key pro-inflammatory mediators including IL-1β, TNF-α and TGF-β and triggered the Tregs cells activation. At the molecular level, long term PTP1B inhibition resulted in a noticeable mitigation of liver ER stress, improvement of mitochondrial dynamics and consequently, a regulation of autophagic response. Similarly, short-term ex vivo treatment of EMS liver explants with Trodusquemine (MSI-1436) substantially enhanced autophagy by upregulating the levels of HSC70 and Beclin-1 at both mRNA and protein level. Moreover, the PTP1B inhibitor potentiated mitophagy and associated expression of MFN2 and PINK1. Interestingly, inhibition of PTP1B resulted in potent attenuation of ER stress key mediators’ expression namely, CHOP, ATF6, HSPA5 and XBP1. Presented findings shed for the first time promising new insights in the development of an MSI-1436-based therapy for proper equine metabolic syndrome intervention and may additionally find potential translational application to human metabolic syndrome treatment